2023
DOI: 10.1002/oby.23664
|View full text |Cite
|
Sign up to set email alerts
|

Circadian‐mediated regulation of cardiometabolic disorders and aging with time‐restricted feeding

Abstract: Circadian rhythms are present throughout biology, from the molecular level to complex behaviors such as eating and sleeping. They are driven by molecular clocks within cells, and different tissues can have unique rhythms. Circadian disruption can trigger obesity and other common metabolic disorders such as aging, diabetes, and cardiovascular disease, and circadian genes control metabolism. At an organismal level, feeding and fasting rhythms are key drivers of circadian rhythms. This underscores the bidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…All statistical analyses were performed with GraphPad Prism 9. Significance in cardiac function was determined using one-way ANOVA with two-sided unpaired T-test as previously described 6,[10][11][12] . To rule out sex-specific differences, our analysis will be carried out in both male and female flies.…”
Section: Statistics and Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…All statistical analyses were performed with GraphPad Prism 9. Significance in cardiac function was determined using one-way ANOVA with two-sided unpaired T-test as previously described 6,[10][11][12] . To rule out sex-specific differences, our analysis will be carried out in both male and female flies.…”
Section: Statistics and Reproducibilitymentioning
confidence: 99%
“…Moreover, mutant flies carrying genetic variants that are associated with a higher risk for CVD result in a similar outcome in the fly 3,4,6 . Furthermore, flies like humans living in industrial societies, consume some of their daily caloric intake at night and nutritional challenges that compromise cardiac function in humans have similar effects on flies [10][11][12] .…”
mentioning
confidence: 99%
“…Emerging literature has suggested that restricting the timing of food intake and aligning food intake with circadian rhythms can improve metabolic health parameters and activate cellular pathways similar to that of CR, without calorie counting [20,21]. However, recent findings from randomized controlled trials (RCTs) that have compared energy-matched TRE interventions with CR have suggested that the metabolic benefits of TRE can be accounted for solely by the observed reduction in energy intake [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mutant flies carrying genetic variants that are associated with a higher risk for CVD result in a similar outcome in the fly 3,4,6 . Furthermore, flies like humans living in industrial societies, consume some of their daily caloric intake at night and nutritional challenges that compromise cardiac function in humans have similar effects in flies [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%